Le travail des enfants en Afrique subsaharienne et la responsabilité internationale des entreprises multinationales - Kouassi, Danielle-Esther Niangoran (Université de Montréal, 2025)
Les droits de l’enfant occupent aujourd’hui une place centrale dans le domaine des droits de la personne. De nombreuses conventions ont été adoptées pour protéger les enfants et leur reconnaître des droits spécifiques à leur condition. C’est ainsi que l’idée de l’interdiction du travail des enfants a été introduite, ce travail nuit à leur développement physique et mental ainsi qu’à leur éducation. Plusieurs organismes internationaux, comme l’Organisation des Nations Unies (ONU) et l’Organisation Internationale du Travail (OIT), se sont engagés à lutter contre ce phénomène. Cependant, en Afrique subsaharienne, cette lutte rencontre de nombreux obstacles et le travail des enfants y est encore monnaie courante. Face à cette situation, la communauté internationale (États, organismes internationaux, organisations non gouvernementales, etc.) a entrepris de nombreuses actions. Malheureusement, celles-ci ont une efficacité limitée en raison de l’absence d’implication d’acteurs primordiaux : les entreprises multinationales. Elles occupent une place de plus en plus importante sur la scène internationale et une partie de ces entreprises profite de l’exploitation des enfants dans les pays d’Afrique subsaharienne sans pour autant reconnaître ce phénomène ou leur implication directe ou indirecte. Aussi, l’état actuel du droit, plus précisément du droit international, rend difficile, voire impossible d’engager leur responsabilité. Ce travail de recherche va donc s’intéresser de plus près aux insuffisances des normes internationales adoptées et à la nécessité d’engager la responsabilité de ces entreprises du point de vue du droit international.
Keywords: Child labor; Children's rights; Conventions de l’OIT; Corporate Social Responsibility; Droits des enfants; Economic exploitation; Entreprises multinationales; Exploitation économique; Human rights violations; ILO conventions; International responsibility; Litiges transnationaux; Multinational corporations; Multinationales; Organisation international du travail; Responsabilité internationale; Transnational litigation; Travail des enfants; Violations des droits humains; international labor organization

Proposed legal reforms to protect South Africa's informal social security - Zeelie, Robin Erin (University of Pretoria, 2024)
Informal social security is a non-governmental form of social security between kin and/or community members and is a prevalent practice in South Africa. The question this dissertation analyses is whether the South African government fails in its constitutional duty to protect and advance informal social security. The dissertation limits itself to analysing cash transfers through social grants, and social insurance in the Unemployment Insurance Act and the Compensation for Occupational Injuries and Diseases Act. This dissertation delineates its definition of informal social security, historically contextualises its practice, and explains the contemporary formal social security framework. This dissertation finds five prominent shortcomings in the formal framework, and that these shortcomings have a profoundly negative, weakening effect on informal social security, as the more people who rely on informal mechanisms, the less it can respond to needs arising from life contingencies, shocks, and risks. The dissertation concludes by analysing three legal reform proposals the state can implement: extending existing social insurance frameworks to those in the informal sector, promoting cooperatives as a formal platform for the informal, and the basic income grant.
Keywords: Basic income grant; Cooperatives; Duty; History; Informal social security; Republic of South Africa; Social assistance; Social security

The Influence of Corporate Sustainability Laws on Multi-Stakeholder Initiatives to Eliminate Forced and Child Labour in Supply Chains - Fanou, Temisan (McMaster University, 2024)
An array of governance initiatives has emerged to address forced labour and labour exploitation in global value chains (GVCs). Drawing on the transnational business governance interactions theoretical framework, as well as Timothy Bartley’s place-conscious transnational governance model, this thesis examines the interaction between two of these hybrid forms of governance: multi-stakeholder initiatives and corporate sustainability laws. I conduct a case study of the cocoa sector, and specifically of the multinational company, Nestlé, using multiple qualitative research methods including legal analysis, key informant interviews, and documentary analysis. My research suggests that the layering of corporate sustainability laws, and particularly the French Duty of Vigilance Law, on top of CSR and MSIs in the cocoa sector, is not addressing the governance gap that permits corporations to evade accountability for human rights abuses in their supply chain. I find that the introduction of corporate sustainability laws may have contributed to a decrease in Nestlé's efforts to address labor violations in certain areas, while in others, it appears to have supported the continuation of existing practices. This raises implications for the continuous efforts in various jurisdictions to introduce these laws as a solution to the shortcomings of private, voluntary rule-making systems. Further research is required to explore how these governance mechanisms are interacting in other sectors, in companies of different sizes, and within various types of MSIs. This will help identify the factors that influence interactions and shed further light on the path forward for policymakers.

Attaining effective and speedy resolutions of unfair dismissal disputes in Lesotho: An explorarion of possible lessons from South Africa - Ntaitsane, Mamolefi Anacletta (National University of Lesotho, 2023)
National Manpower Development Secretariat
Keywords: Labour dispute; Lesotho; Resolution mechanisms; Unfair dismissal disputes

Ley rider : dependencia y ajenidad en las nuevas relaciones laborales del entorno digital - Muriel Díaz, Pablo (Universidad Internacional de Andalucía, 2021)
La presente monografía analiza el régimen jurídico instaurado tras la entrada en vigor de la Ley 12/2021, de 28 de septiembre, por la que se modifica el texto refundido de la Ley del Estatuto de los Trabajadores, aprobado por el Real Decreto Legislativo 2/2015, de 23 de octubre, para garantizar los derechos laborales de las personas dedicadas al reparto en el ámbito de las plataformas digitales, que añade una Disposición Adicional 23ª al texto del Estatuto de los Trabajadores, consagrando a nivel legal la presunción de laboralidad de las relaciones entre trabajador y empresa en el ámbito de las plataformas digitales de reparto. Además, la norma jurídica viene a modificar el artículo 64.4 del Estatuto de los Trabajadores, introduciendo un nuevo apartado bajo la letra d), ampliando así el derecho de información de los comités de empresa, en su condición de máximo órgano de representación del conjunto de los trabajadores. Por otra parte, el trabajo centrará sus esfuerzos en desgranar la adaptación o reformulación de los clásicos conceptos jurídicos de Derecho del Trabajo de dependencia y ajenidad, como características esenciales del trabajo asalariado o por cuenta ajena, frente al trabajo por cuenta propia, clave fundamental para determinar, en definitiva, la existencia o no de una relación de naturaleza laboral. Utilizando como principal referencia la Sentencia número 805/2020, de fecha 25 de septiembre de 2020, del Tribunal Supremo, Pleno de la Sala de lo Social (recurso número 4746/2020), en cuyos principios se ha inspirado la posterior norma jurídica, trataremos de analizar la evolución que han sufrido estos conceptos a raíz del imparable auge del modelo de relaciones laborales surgido a la sombra de la economía tecnológica y del entorno digital, especialmente, en el ámbito de las plataformas de reparto de mercancías y toda clase de productos de consumo.